Splitting of the P3 component during dual-task processing in a patient with posterior callosal section. - Hesselmann, Guido; Naccache, Lionel; Cohen, Laurent; Dehaene, Stanislas (Cortex: A Journal Devoted to the Study of the Nervous System & Behavior, 2013)
When two concurrent sensorimotor tasks have to be performed at a short time interval, the second response is generally delayed at a central decision stage. However, in patients who have undergone full or partial transection of forebrain fibers connecting the two hemispheres (split-brain), independent structures subserving all processing stages should reside in each disconnected hemisphere, thus predicting parallel processing of dual tasks. Surprisingly, this prediction is usually not verified behaviorally. We reasoned that brain imaging with high-density recordings of event-related potentials (ERPs) could clarify the extent and limits of parallel processing in callosal patients. We studied a patient (AC) with posterior callosal section in a lateralized number-comparison task. Behaviorally, the split-brain patient showed robust dual-task interference, superficially similar to the psychological refractory period (PRP) effect in the control group of 14 healthy subjects, but significantly different in important aspects such as slowing of response times in the first task. Analysis of ERPs revealed that the parietal P3 component became split into distinct contralateral components in the patient, and was dramatically reduced for targets in his left visual field. In contrast to the control group, P3 latencies showed minimal to nonexistent postponement related to dual-task processing in the patient. In summary, our findings suggest that the left and right hemisphere networks normally involved in a single distributed 'global neuronal workspace' that underlies the generation of the P3 component and serial processing, became strongly decoupled after a posterior callosal lesion.